Knife : meditations after an attempted murder - Rushdie, Salman (New York ; India : Penguin Random House India, 2024)
From internationally renowned writer and Booker Prize winner Salman Rushdie, a searing, deeply personal account of enduring--and surviving--an attempt on his life thirty years after the fatwa that was ordered against him. Speaking out for the first time, and in unforgettable detail, about the traumatic events of August 12, 2022, Salman Rushdie answers violence with art, and reminds us of the power of words to make sense of the unthinkable. Knife is a gripping, intimate, and ultimately life-affirming meditation on life, loss, love, art--and finding the strength to stand up again.
During those empty, sleepless nights, I thought a lot about The Knife as an idea. A knife was a tool, and acquired meaning from the use we made of it. Language, too, was a knife. It could cut open the world and reveal its meaning, its inner workings, its secrets, its truths. It could cut through from one reality to another. It could call bullshit, open people's eyes, create beauty. Language was my knife. If I had unexpectedly been caught in an unwanted knife fight, maybe this was the knife I could use to fight back.--Back cover.
Part one: The angel of death. Knife -- Eliza -- Hamot -- Rehab -- Part two: The angel of life. Homecoming -- The A. -- Second chance -- Closure?
Donated by Farhana Zahir, Assistant Professor, BRAC Business School, BRAC University
Keywords: Rushdie, Salman; Rushdie, Salman -- Assassination attempts; Authors, English -- 20th century -- Biography; Attempted assassination -- New York (State) -- Chautauqua; Attempted murder -- New York (State) -- Chautauqua; Écrivains anglais -- 20e siècle -- Biographies; Tentatives d'assassinat -- New York (État) -- Chautauqua; Tentative de meurtre -- New York (État) -- Chautauqua; BIOGRAPHY & AUTOBIOGRAPHY -- Personal Memoirs; BIOGRAPHY & AUTOBIOGRAPHY -- Cultural, Ethnic & Regional -- General; Memoirs; Ethnic studies; Autobiographies; autobiographies (literary works)